Swarm-based descriptor combination and its application for image classification - Mansano, Alex Fernandes [UNESP]; Matsuoka, Jéssica Akemi [UNESP]; Abiuzzi, Nikolas Aleksander da Mota [UNESP]; Afonso, Luis Cláudio Súgi [UNESP]; Papa, João Paulo [UNESP]; Faria, Fabio Augusto; Torres, Ricardo da Silva; Falcão, A. X. (Universitat Autonoma de Barcelona, 2014)
In this paper, we deal with the descriptor combination problem in image classification tasks. This problem refers to the definition of an appropriate combination of image content descriptors that characterize different visual properties, such as color, shape and texture. In this paper, we propose to model the descriptor combination as a swarm-based optimization problem, which finds out the set of parameters that maximizes the classification accuracy of the Optimum-Path Forest (OPF) classifier. In our model, a descriptor is seen as a pair composed of a feature extraction algorithm and a suitable distance function. Our strategy here is to combine distance scores defined by different descriptors, as well as to employ them to weight OPF edges, which connect samples in the feature space. An extensive evaluation of several swarm-based optimization techniques was performed. Experimental results have demonstrated the robustness of the proposed combination approach.
Keywords: Image classification; Descriptor combination; Swarm intelligence; Optimum-path forest